Penguatan Pemahaman Warga Desa Manggarmas kecamatan Godong, Grobogan, Jawa Tengah tentang Hak dan Kewajiban Warga Negara dalam Perspektif Gender - Juita, Subaidah Ratna; santosa, Agung; Izziyana, Wafda Vivid (Fakultas Hukum Universitas Semarang, 2024)
The purpose of this community service is to provide an understanding of rights and duties, which are two essential concepts in social life, including in the context of citizenship. In Indonesia, the rights and duties of citizens are regulated in the 1945 Constitution and various other laws. Citizens' rights can be understood as all that a citizen is entitled to, either in the form of authority or power. Meanwhile, duties refer to things that must be done as members of society. In general, duties are actions that must be carried out in order to obtain our rights. As Indonesian citizens, we have rights that must be respected and fulfilled, as well as duties that must be carried out as a form of our responsibility to the state and society. Based on a situational analysis, an issue has been identified: the lack of understanding among the residents of Manggarmas Village, Godong District, Grobogan, Central Java, regarding the rights and duties of citizens from a gender perspective. To provide a solution to this issue, the Community Service Team from the Gender and Child Research Center at USM will offer counseling to the residents of Manggarmas Village, Godong District, Grobogan, Central Java, regarding the rights and duties of citizens from a gender perspective.